The relationship between parental investment and high school students' academic achievement: The mediating role of academic emotions and the moderating role of learning motivation - Jing Qian (Acta Psychologica)
This study aimed to clarify how parental investment influences academic achievement through positive academic emotions and whether learning motivation enhances this process. Unlike previous studies that primarily treated learning motivation as a mediator, this study explores its role as a moderator, assessing whether higher learning motivation strengthens the positive effects of emotional experiences on academic achievement. Data were collected from 698 high school students across five schools in Anhui Province, China, using standardized questionnaires and midterm exam scores. Mediation and moderation analyses revealed that positive academic emotions served as a partial mediator in the relationship between parental investment and academic achievement. Additionally, learning motivation significantly moderated the interaction between parental investment and positive academic emotions, while also affecting the indirect impact of these emotions on academic achievement. These findings suggest that enhancing learning motivation can amplify the beneficial impact of parental investment on academic achievement through emotional pathways, providing a more comprehensive understanding of how emotional and motivational processes interact.